2010
DOI: 10.1016/j.schres.2010.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity and increased risk for schizophrenia in Egypt

Abstract: Background Consanguinity has been suggested as a risk factor for psychsoses in some Middle Eastern countries, but adequate control data are unavailable. Our recent studies in Egypt have shown elevated parental consanguinity rates among patients with bipolar I disorder (BP1), compared with controls. We have now extended our analyses to Schizophrenia (SZ) in the same population. Methods A case-control study was conducted at Mansoura University Hospital, Mansoura, Egypt (SZ, n = 75; controls, n = 126, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 30 publications
4
36
0
3
Order By: Relevance
“…The rate of parental consanguinity (43.8 vs. 38%) and the mean coefficient of inbreeding (0.0198 ± 0.29 vs. 0.015 ± 0.24) was higher among Sz patients compared to subjects without Sz (table 1). Similar to our results, a significant elevated rate of consanguinity was observed among Sz patients in Egypt [5]. The present study has confirmed that consanguinity contributes to a high incidence of Sz in offspring.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of parental consanguinity (43.8 vs. 38%) and the mean coefficient of inbreeding (0.0198 ± 0.29 vs. 0.015 ± 0.24) was higher among Sz patients compared to subjects without Sz (table 1). Similar to our results, a significant elevated rate of consanguinity was observed among Sz patients in Egypt [5]. The present study has confirmed that consanguinity contributes to a high incidence of Sz in offspring.…”
Section: Discussionsupporting
confidence: 92%
“…Historically, medical concerns about the deleterious effects of more closely inbred marriages have focused on the risk posed by recessive Mendelian traits, with much less attention to complex disorders and continuous traits (Bittles and Black, 2010). Among the few examples of complex traits however is good, casematched DNA-backed, evidence for an elevated risk for some psychiatric disorders among individuals with consanguineous parentage (Mansour et al, 2009(Mansour et al, , 2010. There appear to be some positive health outcomes associated with consanguineous marriages, such as higher fertility (reviewed in Bittles et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have confirmed these findings and shown that consanguinity is a risk factor for cardiovascular disease (Shami, Qaisir and Bittles, 1991), bipolar disorder 1 (Mansour et al, 2009), schizophrenia (Mansour et al, 2010) and Alzheimer disease (Farrer et al, 2002). These results may be relevant to the high prevalence of mental and cardiovascular disorders in the Habsburg-Bourbon-Braganzas of Portugal.…”
Section: Consanguinitymentioning
confidence: 77%